The Two Reproductions in (Feminist) Art and Theory since the 1970s. Issue 1 (2nd January 2017) - Vishmidt, Marina
Abstract: This article approaches the optic of 'reproduction' in feminist theory and politics from two sides: a) the discussion of social reproduction currently at the top of the agenda of materialist feminisms, that is as a specific modality of gendered, racialised and often unwaged labour; and b) the sense in which social reproduction can be taken as the 'reproduction of the conditions of production', in Louis Althusser's analysis. These two approaches to the question of reproduction are used to open a path to a sample of historical and contemporary art practices, readable either in terms of a feminist deployment of reproduction as a spectrum of gendered tasks, or in terms of performing the impasses of a kind of social 'non-reproduction' that belongs to the second type, with the social reproduction perspective assuming the function of institutional or, perhaps, 'infrastructural' critique. The article covers the period between the 1970s and the present.